Association of Midlife Inflammatory Markers With Cognitive Performance at 10-Year Follow-up. (15th November 2022) - Kipinoinen, Teemu; Toppala, Sini; Rinne, Juha O.; Viitanen, Matti H.; Jula, Antti M.; Ekblad, Laura L.
Abstract : Background and Objectives: Chronic low-grade inflammation, commonly associated with cardiovascular diseases and risk factors, has been associated inconclusively with cognitive decline and dementia. The aim of our study was to evaluate whether low-grade inflammation, measured in midlife, is associated with a decline in cognitive performance after a 10-year follow-up. We hypothesized that low-grade inflammation, estimated by interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), and high-sensitivity CRP (hs-CRP), is a predictor of cognitive decline in the general population. Methods: This prospective cohort study is based on a Finnish nationwide, population-based Health 2000 Examination Survey, its supplemental examinations in 2000–2001, and the follow-up Health 2011 Survey. Cognitive performance at baseline and at follow-up was assessed with categorical verbal fluency (VF), word-list learning (WLL), and word-list delayed recall (WLDR). Baseline low-grade inflammation was measured with IL-6, TNF-α, and hs-CRP in 2001. Associations between low-grade inflammation and cognitive performance were analyzed with multivariable linear models adjusted for age, sex, education, APOE ε4 genotype, type 2 diabetes, hypertension, hypercholesterolemia, body mass index, depressive symptoms, smoking, and baseline cognition. Results: Nine hundred fifteen participants aged 45–74 years (median age 54 years, 55% women) were included in the analysis. Both higher IL-6 and TNF-α at baseline predicted poorer performance in VF and WLL at 10-year follow-up (VF: IL-6 β: −1.14, p = 0.003, TNF-α β: −1.78, p = 0.008; WLL: IL-6 β: −0.61, p = 0.007, TNF-α β: −0.86, p = 0.03). Elevated IL-6 also predicted a greater decline in VF and WLL after a 10-year follow-up (VF: β: −0.81, p = 0.01; WLL: β: −0.53, p = 0.008). Baseline TNF-α did not predict cognitive decline, and hs-CRP did not predict cognitive performance or decline after 10-years. Discussion: Our results suggest that low-grade inflammation in midlife is an independent risk factor for poorer cognitive performance later in life. Of the studied markers, IL-6 and TNF-α seem to be stronger predictors for cognitive performance and decline than hs-CRP.